Effects of Grazing Enclosures on Species Diversity, Phenology, Biomass, and Carrying Capacity in Borana Rangeland, Southern Ethiopia - Fenetahun, Yeneayehu; Yuan, You; Xinwen, Xu; Yongdong, Wang (Frontiers in Ecology and Evolution, 2021)
Livestock grazing activity is the major threatening of species diversity and degradation the Borana rangeland, Southern Ethiopia. Grazing enclosure is one of most implementing techniques to restore degraded rangelands through changing the composition, abundance, and diversity of species. However, the effect of grazing enclosure in different intensity and duration compared with the open-grazing rangelands are poorly known. we established five plots in each treatment to examine the effect of grazing enclosure on grass species height, abundance, diversity, phenology, biomass, heterogeneity, and carrying capacity of rangeland under grazed and enclosed conditions. We found showed that grazing enclosure significantly increased grass height, abundance, biomass, carrying capacity, phenological period, and species diversity. However, increment of height, diversity, and phenological periods were not consistent with enclosure duration and high increment recorded within short-term enclosure site. Long-term grazing enclosure significantly reduced species diversity. Both evenness and dominance index varied little within enclosure sites but not significant. In addition, grass community heterogeneity was significantly higher in long-term grazing enclosure, this is because of decreasing of species diversity. In general, our result addressed the gap of the effects of grazing enclosure while using management strategy and are dependent on enclosure duration. And also contributes to the growing theoretical basis and recommend strategies like rotational grazing and reseeding to be used in tandem with grazing enclosure for sustainable management of rangelands.